Individual placement and support in Italian young adults with mental disorder: Findings from the Reggio Emilia experience. Issue 5 (23rd October 2019) - Pelizza, Lorenzo; Ficarelli, Maria L.; Vignali, Elisabetta; Artoni, Simona; Franzini, Maria C.; Montanaro, Serenella; Andreoli, Maria V.; Marangoni, Sara; Ciampà, Elizabeth; Erlicher, Diana; Troisi, Elisa; Pupo, Simona
Abstract: Aim: Individual placement and support (IPS) has a considerable body of evidence for its effectiveness in helping people with mental disorder to achieve and maintain competitive jobs. However, little data in young adult populations are currently available, especially in Europe. Aim of this study was to assess the effect of IPS in Italian young adults with moderate‐to‐severe mental illness, examining the main competitive employment outcomes and drop out rates during a 3‐year follow‐up period. Methods: Participants (n = 54) were recruited from patients receiving psychiatric treatment in one of the seven adult Community Mental Health Centers of the Reggio Emilia Department of Mental Health. Together with drop out rates, we investigated job duration (total number of days worked), job acquisition (employment in the labour market for at least 1 day during the follow‐up), total hours per week worked, and job tenure (weeks worked on the longest‐held competitive job). Results: A crude competitive employment rate of 40.7% and a crude drop out rate of 22.2% over the 3‐year follow‐up period were found. However, 66% of 42 clients who remained in the program over 3 years gained competitive employment at some time during the 3‐year period. Conclusions: This research shows the feasibility of an IPS intervention model in the public mental health care system in Italy, especially for a young adult target population.